Real-time breath gas analysis for pharmacokinetics: monitoring exhaled breath by on-line proton-transfer-reaction mass spectrometry after ingestion of eucalyptol-containing capsules. - Beauchamp, Jonathan; Kirsch, Frauke; Büttner, Andrea (Journal of Breath Research, 2010)
Eucalyptol (1,8-cineole) is a common active agent in non-prescription pharmaceutical products that is employed to clear the airways during mucus blockages. Following ingestion of a eucalyptol-containing capsule, the capsule dissolves in the gut and transfers eucalyptol into the blood, which is subsequently expelled via the lungs, thus exposing this decongesting and inflammation-abating compound to the airways. The breath gas concentrations of eucalyptol in 11 healthy adult volunteers were monitored at regular intervals after capsule ingestion using on-line proton-transfer-reaction mass spectrometry (PTR-MS). Eucalyptol appeared in exhaled breath gas at varying times following ingestion, with its onset ranging from 1 h and 6 min to 4 h and 48 min (mean ± SD: 2.1 ± 0.5 h). Maximum concentrations also varied greatly, with peak eucalyptol levels between 106 and 1589 ppb(v) (mean ± SD: 489 ± 319 ppb(v)). These variations were not only inter-subject, but also intra-subject, i.e. repeated tests with the same participant yielded different onset times and a broad range of concentration maxima. A considerable contribution to these variations from infrequent sampling and analysis is discussed. This study characterized the temporal transfer of eucalyptol via the blood into the airways by examining exhaled breath and thereby demonstrated the suitability of on-line breath gas analyses, particularly PTR-MS, for certain pharmacokinetic investigations.